Perancangan UI/UX Aplikasi Jasa Desain Grafis Berbasis Mobile Dengan Design Science Research Methodology - Rizan Ramdani; Resmi , Mochzen Gito; Jaelani, Irsan (UNIKA Santo Thomas, 2023)
Most freelance designers in Indonesia use websites, freelance applications, or get clients from acquaintances. Currently there are still few adequate applications in Indonesia to facilitate and become a bridge between designers and clients, and also tend to focus on buyers only. Intense competition between designers on freelance service websites also means that only a handful of designers dominate and get clients. There needs to be an easy-to-use application that can be accessed on mobile phones and has various payment methods to open up new opportunities for novice Indonesian designers and people who need designs, by making UI and UX designs in advance it is expected to produce designs that suit their needs and make it easy for users. This study applies the design science research methodology, according to Ken Peffers et al. DSRM is a research methodology in the field of design science for information systems that combines principles, practices, and procedures. Testing or testing the researchers tested the system usability scale (SUS). The results of this study are a prototype mobile-based graphic design service application. Based on testing using the SUS method, the average sus value obtained was 81.2. It can be concluded that mobile-based graphic design service applications are acceptable because they meet the acceptable category.